2005
DOI: 10.1083/jcb.200409115
|View full text |Cite
|
Sign up to set email alerts
|

Processing of VEGF-A by matrix metalloproteinases regulates bioavailability and vascular patterning in tumors

Abstract: Vascular endothelial growth factor (VEGF) is a critical mediator of blood vessel formation during development and in pathological conditions. In this study, we demonstrate that VEGF bioavailability is regulated extracellularly by matrix metalloproteinases (MMPs) through intramolecular processing. Specifically, we show that a subset of MMPs can cleave matrix-bound isoforms of VEGF, releasing soluble fragments. We have mapped the region of MMP processing, have generated recombinant forms that mimic MMP-cleaved a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
631
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 642 publications
(670 citation statements)
references
References 51 publications
(52 reference statements)
36
631
0
3
Order By: Relevance
“…MMP19 was reported to efficiently cleave VEGF into smaller fragments. 33 However, the reduced expression of VEGF in the conditioned media with WT MMP19 in this study was not likely due to the cleaving activity of the MMP19 on VEGF, since no small fragments were detected in conditioned media of WT MMP19 clones. Instead, MMP19 may down-regulate VEGF secretion by retaining VEGF in the ECM.…”
Section: Discussionmentioning
confidence: 56%
“…MMP19 was reported to efficiently cleave VEGF into smaller fragments. 33 However, the reduced expression of VEGF in the conditioned media with WT MMP19 in this study was not likely due to the cleaving activity of the MMP19 on VEGF, since no small fragments were detected in conditioned media of WT MMP19 clones. Instead, MMP19 may down-regulate VEGF secretion by retaining VEGF in the ECM.…”
Section: Discussionmentioning
confidence: 56%
“…This finding was initially unexpected, as the PDGF-DD(GFD) more potently transformed NIH/3T3 cells in vitro. However, considering that altered pericellular retention and/or matrix interactions are important determinants for the physiological action of many other growth factors (LaRochelle et al, 1991;Ostman et al, 1991;Carmeliet et al, 1999;Grunstein et al, 2000;Lindblom et al, 2003;Lee et al, 2005), this could be a likely mechanism for controlling the function of PDGF-DD as well. In line with this, one could speculate that the observed differences in foci morphology induced by the two PDGF-DD forms are due to different spatial distribution, especially as we have previously shown that smaller and unevenly shaped foci can be formed from NIH/3T3 cells overexpressing matrix-bound PDGF-BB (Li et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Uncleaved VEGF is enriched in at least one MMP9-mutant postnatal tissue, the hypertrophic chondrocyte zone 38 , which indicates that VEGF is an important downstream effector, and possibly a substrate, of MMP9. Truncated VEGF has different effects on tumour blood vessels than does uncleavable VEGF; truncated VEGF increases vessel diameter, whereas uncleavable VEGF increases vessel sprouting 64 . Mmp9-null mice display defective post-embryonic neovasculature, suggesting that in wild-type mice, postnatal blood vessels respond differently to cleaved and uncleaved forms of VEGF.…”
Section: Mmps and Vegf Signalingmentioning
confidence: 98%
“…d | MMPs can activate or modify the action of latent signalling molecules, resulting in diverse cellular consequences. For example, cleavage of vascular endothelial growth factor (VEGF) by MMPs changes angiogenic outcome by modifying the binding and diffusion properties of VEGF 64 . e | MMPs can deactivate or modify the action of active signalling molecules, resulting in changes in proliferation, cell death, differentiation or cell motility.…”
Section: Mmp Degradomementioning
confidence: 99%